Peningkatan Mutu Fisiologis dan Daya Simpan Benih serta Ketahanan Patogen dan Agen Hayati pada Benih Padi Berpelapis - Palupi, Tantri; Ilyas, Satriyas; Machmud, Muhammad; Widajati, dan Eny (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTXanthomonas oryzae pv. oryzae (Xoo), is a seedborne pathogen causing bacterial leaf blight (BLB) disease, and reduces the quality of seed and rice production. One of the efforts to control the BLB disease and to improve the quality Xoo infected seeds is the seed coating technique enriched with biological agents. The experiment was aimed to study the effect of coating on seed quality and storage life, as well as the Xoo and biological agents resistence (P. diminuta A6 and B. subtilis 5/B) on the seeds. The experiment was carried out from August 2011 to March 2012, using a split plot design with four replications. The main plot was storage period, i.e. 0, 1, 2, 3, 4, 5, 6, and 7 months. The sub plot was seed coating treatment consisted of negative control (healthy seed); positive control (seeds contaminated with Xoo); seed infested with biological agens; alginate 3% + 1% peat + biological agents; arabic gum 3% + 1% gypsum + biological agents; CMC 1.5% + 1% talc + biological agents; and bactericide streptomycin sulfat 20%. The coated seeds were stored an air-conditioned room (18-20 °C, RH 48-50%). The results showed that the treatments were able to maintain seeds quality during storage, i.e. germination percentage, uniformity percentage, and vigor index, better than those of the positive control. The P. diminuta A6 was still presence (0.08 x 106 cfu mL-1) in seeds coated after 7 month storage, and the B. subtilis 5/B was still presence (0.07 x 106 cfu mL-1) up to 6 month storage with 3% arabic gum + 1% gypsum + biological agents. Keywords: Bacillus subtilis 5/B, Pseudomonas diminuta A6, seed quality, storage space, Xanthomonas oryzae pv. oryzae